Management of Complex Urethral Stricture Disease: Take the Challenge - Islam, Md waliul (Bangladesh Journal of Urology, 2020)
Abstract Not Available Bangladesh Journal of Urology, Vol. 16, No. 2, July 2013 p.35-36